Acetylcholine-induced endothelium-dependent contractions in the SHR aorta: the Janus face of prostacyclin - Gluais, Pascale (2005)
1. In the spontaneously hypertensive rat (SHR) and aging Wistar–Kyoto rats (WKY), acetylcholine releases an endothelium-derived contracting factor (EDCF) produced by endothelial cyclooxygenase-1, which stimulates thromboxane A(2) receptors (TP receptors) on vascular smooth muscle. The purpose of the present study was to identify this EDCF by measuring changes in isometric tension and the release of various prostaglandins by acetylcholine. 2. In isolated aortic rings of SHR, U 46619, prostaglandin (PG) H(2), PGF(2α), PGE(2), PGD(2), prostacyclin (PGI(2)) and 8-isoprostane, all activate TP receptors of the vascular smooth muscle to produce a contraction (U 46619≫8-isoprostane=PGF(2α)=PGH(2)>PGE(2)=PGD(2)>PGI(2)). The contractions produced by PGH(2) and PGI(2) were fast and transient, mimicking endothelium-dependent contractions. PGI(2) did not relax isolated aortic rings of WKY and SHR. 3. Acetylcholine evoked the endothelium-dependent release of thromboxane A(2), PGF(2α), PGE(2), PGI(2) and most likely PGH(2) (PGI(2)≫PGF(2α)⩾PGE(2)>TXA(2)>8-isoprostane, PGD(2)). Dazoxiben abolished the production of thromboxane A(2), but did not influence the endothelium-dependent contractions to acetylcholine. 4. The release of PGI(2) was significantly larger in the aorta of SHR than in WKY, and the former was more sensitive to the contractile effect of PGI(2) than the latter. The inhibition of PGI-synthase was associated with an increase in PGH(2) spillover and the enhancement of acetylcholine-induced endothelium-dependent contractions. 5. Thus, in the aorta of SHR and aging WKY, the endothelium-dependent contractions elicited by acetylcholine most likely involve the release of PGI(2) with a concomitant contribution of PGH(2).